The Importance of Surveillance in the Control of Influenza - Claude Hannoun (Canadian Journal of Infectious Diseases)
Surveillance of influenza has important practical uses for controlling the spread and the severity of epidemic episodes. The participation of sentinel practitioners directly involved in primary patient care is essential and can be promoted by active surveillance networks working in real time with a strong coordinating structure. The Groupes régionaux d’observation de la Grippe (grog) system, elaborated in France since 1984 on these principles, has allowed a short and middle term prevision of outbreaks and the isolation of a large number of influenza strains.